(untitled) (Journal of Pharmaceutical Negative Results, 2022)
We examine how the Climate Change affected on the Agricultural Production , and how the impact of climatic changes on the productivity of the most important grain crops in Egypt, with the aim of determining the extent to which productivity has changed due to climate change in Egypt, using the Autoregressive Distributed lagged methodology (ARDL), where it was found that there is an inverse relationship between climate changes and the productivity of the most important cereal crops, a relationship that is consistent with the economic logic. The results indicate that a similar negative impact of the maximum temperature change on the productivity of the most important cereal crops in the long term, which is consistent with an economic theory.